2013
DOI: 10.1097/bth.0b013e318284dbd7
|View full text |Cite
|
Sign up to set email alerts
|

Early Active Mobilization Following UCL Repair With Mitek Bone Anchor

Abstract: Ulnar collateral ligament (UCL) injuries of the thumb are common. Surgical repair is accepted as the treatment of choice for complete rupture of the ligament. Biomechanical studies have suggested that Mitek bone anchor repairs are potentially safe and strong enough to allow early controlled active mobilization. To date, there have been no studies to compare early active mobilization following Mitek bone anchor repair to standard postoperative rehabilitation involving thumb spica immobilization for the first 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…For instable bony avulsions or complete ruptures in an acute setting, surgical treatment is favoured, as it has yielded excellent results [22, 26]. Bone anchors are currently most commonly used for surgical repair in proximal or distal ligament avulsions, whereas mid-substance tears can also be sutured directly.…”
Section: Introductionmentioning
confidence: 99%
“…For instable bony avulsions or complete ruptures in an acute setting, surgical treatment is favoured, as it has yielded excellent results [22, 26]. Bone anchors are currently most commonly used for surgical repair in proximal or distal ligament avulsions, whereas mid-substance tears can also be sutured directly.…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics of the included trials including the interventions and comparators are provided in Table 1 . Of the three randomised controlled trials, two assessed the outcomes of different rehabilitation regimes in patients who had been exclusively treated with surgery 13 , 14 . The remaining RCT assessed the outcome in patients managed both surgically and non-surgically, who were randomised to treatment with either a plaster cast or a functional splint 15 .…”
Section: Resultsmentioning
confidence: 99%
“…53 Suture anchors provide predictable and reliable fixation with the ability to allow active range of motion early in the rehabilitation period. 55,56 Complications are few and include failure of primary repair, infection, paresthesias on the radial border of the thumb, and decreased range of motion. 2,14,23,53,57 CHRONIC ULNAR COLLATERAL LIGAMENT RECONSTRUCTION Injuries greater than 3 weeks old have historically had poor outcomes with surgical repair, presumably because of attenuation of the remnant ligament.…”
Section: Acute Ulnar Collateral Ligament Repairmentioning
confidence: 98%
“…Recent evidence has shown that early active range of motion is safe following suture anchor fixation. 56,67 In this protocol, the forearm-based thumb spica splint is removed at postoperative day 3 to 5 and is replaced by a removable thermoplastic splint. Patients are instructed to come out of the splint 4 times per day for active range of motion exercises.…”
Section: Postoperative Managementmentioning
confidence: 99%